Republic of Slovenia : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that the economic growth of Slovenia slowed in 2001 from about 4.5 percent to about 3 percent as domestic demand fell sharply and external demand weakened. Competitiveness remained strong and the current account deficit narrowed to about 1\2 percentage point of GDP. Real export growth decelerated from 12.7 percent in 2000 to 7.9 percent in the first three quarters of 2001. The planned reduction in the budget deficit in 2001 did not materialize because of expenditure overruns.